Digital microfluidics for time-resolved cytotoxicity studies on single non-adherent yeast cells1. Issue 8 (21st April 2015) - Kumar, P. T.; Vriens, K.; Cornaglia, M.; Gijs, M.; Kokalj, T.; Thevissen, K.; Geeraerd, A.; Cammue, B. P. A.; Puers, R.; Lammertyn, J.
<x xml:space="preserve">Abstract</x> We demonstrate the application of digital microfluidic technology as a suitable platform for conducting high-throughput cell-based studies on non-adherent yeast cells in a spatio-temporal manner.